O impacto da instrução normativa MPOG nº 3/2011 na economia gerada pelo pregão eletrônico nas aquisições públicas federais - Campos, Reinner Ferreira (2015)
The current dissertation delas with electronic trading in federal public administration field and the potential impact on economy credited to the aplication of the related modality after implementing the Normative Instruction nº 3/2011 by Planning and Budget Managment Ministry (PBMM) that imposed na at least 20 seconds break between one same attendant’s bids, on a same item, during the public session of this related modality. This Normative Instruction came as na answer of PBMM to the Court Union Accounts’ determination, which led to that ministry to change the platform that promotes federal electronic trading implementing a device that could obstruct what that account court classified as cheating on bidding process, refering to a software known as “robot”, that allows human operator unpractical while bids, which according to Court Union Accounts, would represent a disappointment to the competitive edge by putting attendants who use the software ahead over those who did not have. To measure if the changing dynamics impacted the federal economy credited to the electronic trading use, the same federal government measurement metodology was used. Acquisition data of the national food basket were observed, according to DIEESE, two years before the NI 3/2011 implementation and two years after this, which meant 18.759 registries between 2010 and 2013. The results show change in the pattern of the economy credited to that form of bidding in electronic form after the implementation of Instruction No. 3/2011 , pointing a positive impact on the economy credited to the use of electronic trading among the universe of analyzed items. At the end of this thesis, we purpose to elaborate new studies aiming to analyze, possibly from the viewpoint of the theory of auctions, and evaluate The reasons That changed the standard in the saving generated by the electronic trading after its changing dynamics.